Rural settlements on Mount Carmel in antiquity - Dar, Shimʻon, (Archaeopress archaeology., 2014)
In the years 1983-2013, an archaeological expedition under the auspices of the Department of Land of Israel Studies and Archaeology of Bar-Ilan University, Ramat Gan, was active on Mount Carmel, Israel. The expedition comprised archaeologists, team members, students and other professionals, as well as pupils from schools in the Sharon and Daliyat el-Carmel. This book describes ten rural mountain sites through which it seeks to reconstruct the character of all the settlements on the mountain and at its foot, from the Persian through the Byzantine periods.